2015
DOI: 10.2196/resprot.4600
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Mobile Phone App for Adults That Uses Physical Activity as a Tool to Manage Cigarette Craving After Smoking Cessation: A Study Protocol for a Randomized Controlled Trial

Abstract: BackgroundResults from studies on the effects of exercise on smoking-related variables have provided strong evidence that physical activity acutely reduces cigarette cravings. Mobile technology may provide some valuable tools to move from explanatory randomized controlled trials to pragmatic randomized controlled trials by testing the acute effectiveness of exercise on quitters under real-life conditions. An mHealth app was developed to be used as a support tool for quitters to manage their cigarette cravings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…To date, the effects of smartphone apps for smoking cessation are largely unknown and this study is one of the very few trials that have been undertaken. A number of larger RCTs are underway to assess the effect of smartphone apps for smoking cessation [ 58 - 61 ]. In the near future, the evidence from these studies will be brought together and reviewed to determine the overall effectiveness of mHealth for smoking cessation, under what conditions and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the effects of smartphone apps for smoking cessation are largely unknown and this study is one of the very few trials that have been undertaken. A number of larger RCTs are underway to assess the effect of smartphone apps for smoking cessation [ 58 - 61 ]. In the near future, the evidence from these studies will be brought together and reviewed to determine the overall effectiveness of mHealth for smoking cessation, under what conditions and for whom.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the effectiveness of mHealth interventions for smoking cessation. While preliminary pilot studies of cessation apps using small samples or short follow-up periods [ 35 - 39 ] and protocols of trials in progress [ 40 - 44 ] have been published, no large scale randomized effectiveness trials have, although several are in progress. Despite this, hundreds of cessation smartphone apps are commercially available.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on cessation apps focus on different outcomes such as app usage [ 17 - 19 ], changes in psychological state related to cessation behavior [ 20 - 22 ], and satisfaction with the treatment with an app [ 18 , 20 ]. To date, effectiveness outcomes have been reported in 3 studies with self-reported abstinence [ 17 , 18 , 20 , 23 ], and 1 study protocol with biochemically validated abstinence outcome was found [ 22 ]. Thus, although an initial body of research on the use of cessation apps exists, little is known about the factors that influence the use of cessation apps and the characteristics of the users of these mHealth apps.…”
Section: Introductionmentioning
confidence: 99%